Sistem Informasi Meramalkan Penjualan Barang Dengan Metode Double Exponential Smoothing (Studi kasus: PD. Padalarang Jaya) - Annastasya Lieberty; Radiant V. Imbar (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
PD. Padalarang Jaya is a trading company that sells a variety of daily needs. The company develop an desktop application for point of sales and purchases goods to vendor and also Decision Support System for forecasting stock of goods using the "Double Exponential Smoothing" methods. This application will be applied on an SMS gateway to facilitate PD. Padalarang Jaya and customers get the information. This application build using C # languages and SQL Server database. For Testing the features using blackbox show that this application has been able to meet the expected features. Keywords: Decision Support System, Double Exponential Smoothing, Sales, Purchasing, SMS Gateway